PERANCANGAN SISTEM INFORMASI STOK KONTAINER DENGAN METODE SCRUM PADA PT PUTRA BATAM JASA MANDIRI UTAMA - Sebastian, Erik; Ridho, Muhammat Rasid (Computer Science and Industrial Engineering, 2021)
PT Putra Batam Jasa Mandiri Utama is a Logistics company based in Batam-Indonesia in which PT Putra Batam Jasa Mandiri Utama main focus is Shipping Containers. PT Putra Batam Jasa Mandiri Utama has 2 kinds of services in which this journal will be focusing on Depot Services. PT Putra Batam Jasa Mandiri Utama is facing problems in which the current application that they are using are have a big inconsistencies data problem. For this on-going issue, the researcher is going to use Scrum as the basis for planning and creating this new Inventory Management System based on user feedbacks and improvement from the researcher itself. Feedback from users such as, inconsistencies in data, the lack of export and import stock report feature in the current system itself has made a big gap in PT Putra Batam Jasa Mandiri Utama Depot SOP (Standard Operational Procedure). As for the results, The application that this researcher has developed by using Laravel Framework is an upgrade from what PT Putra Batam Jasa Mandiri Utama is now using, features such as the Dashboard will be included in which it will functions as a main bridgepoint between Admin and Field Tally.